Antidepressant prescribing in the precision medicine era: a prescriber's primer on pharmacogenetic tools. Issue 1 (December 2017) - Bousman, Chad; Forbes, Malcolm; Jayaram, Mahesh; Eyre, Harris; Reynolds, Charles; Berk, Michael; Hopwood, Malcolm; Ng, Chee
Abstract About half of people who take antidepressants do not respond and many experience adverse effects. These detrimental outcomes are in part a result of the impact of an individual's genetic profile on pharmacokinetics and pharmcodynamics. If known and made available to clinicians, this could improve decision-making and antidepressant therapy outcomes. This has spurred the development of numerous pharmacogenetic-based decision support tools. In this article, we provide an overview of pharmacogenetic decision support tools, with particular focus on tools relevant to antidepressants. We briefly describe the evolution and current state of antidepressant pharmacogenetic decision support tools in clinical practice, followed by the evidence-base for their use. Finally, we present a series of considerations for clinicians contemplating use of these tools and discuss the future of antidepressant pharmacogenetic decision support tools.